Wind Tunnel Investigation into the Resistance Analysis of Slender Body Catamaran - Utama, I Ketut Aria Pria; Sutiyo, S; Suwasono, Bagiyo (Department of Naval Architecture - Diponegoro University, 2020)
The Wind tunnel investigation of a slender body catamaran was conducted in order to determine its resistance characteristics, namely the effect of pressure and flow velocity changes for varied hull separation. The catamaran was tested in a wind tunnel belongs to Department of Mechanical Engineering, ITS, with hull separations ofÂ S/L = 0.2 to 0.4 and variation in Reynolds numbers up to 4.46 x 105. Pressure around the hull was measured using pressure tappings and the flow velocity behind the hull was also measured using a PitÃ´t-static tube. The experimental study shows that the pressure coefficient decreases when the hull separation declines and conversely, the flow velocity increases. The tests demonstrated a viscous interaction between the hulls, and form factors for the monohull and catamaran are derived. The demihull exhibited a form factor (1+k) of 1.265 and in the catamaran mode, the measured form factor (1+Î²k) was between 1.416 and 1.403. The results are in agreement with other published data.